Anaerobic digestion of crude glycerol for biohydrogen production - Ahmad, Mohd. Azlan (2016)
Biodiesel has become one of the main interests for the diesel replacement because it is renewable, and can be produced from various sources. However, the rapid acceleration of biodiesel production consequently contributes towards the mass amount of generation of biodiesel by-product; the waste crude glycerol (CG) which consisted high amount of impurities including the heavy metal that may lead to environmental issues. This has raised the concern and also the interest for the researchers and industries to look for the best solution in managing the excessive crude glycerol. This is included to convert the CG into valuable products, chemically or biologically. Anaerobic digestion process for biohydrogen production using biodiesel waste or crude glycerol as sole substrate seems to have a great potential to be explored. Thus, this study used batch anaerobic fermentation approached using biodiesel wastewater sludge containing indigenous mixed bacteria to produce biohydrogen using CG as the main substrate, and to assess the performance of biohydrogen production under different pH, temperature, incubation time, and initial glycerol concentration. The experiments conducted with the biodiesel wastewater sludge and CG sample were collected from Vance Bioenergy Sdn. Bhd. and Carotino Sdn. Bhd, respectively. The results of the preliminary study using both pure and crude glycerol showed that the mixed culture favours crude glycerol than pure glycerol. There was no methane gas generated throughout this study based on the gas chromatography analysis. Thus, the crude glycerol is further used in this study. Results on the effect of various parameters showed that the mixed culture has successfully converted and utilized the CG up to 99% with hydrogen yield (HY) of 1.05 mol H2/mol glycerol utilized with 10 g/l concentration of CG at 48 hours with 37°C. The optimization study showed that, the most significant parameter that influenced the high HY were the pH and temperature. The result of HY at 1.0 – 1.26 mol H2/mol glycerol could be achieved under the pH, incubation time, and temperature range were within 7.0 - 9.0, 30 - 55 hours, and 31 - 38°C respectively